Penggunaan Poisoner sebagai Perawatan Pendahuluan pada Kasus Pergeseran Garis Median disertai Asimetri Wajah - R. Poedji Soegiono (Faculty of Dentistry, Universitas Indonesia, 2015)
There are two different types of midline shifting, dental and skeletal type, which are frequently followed by facial asymmetry and therefore would interfere the esthetics. The cause of midline shifiting is the presence of occlusal interference which might occur in many aspect of malocclusion. This condition may lead to a habitual occlusion that eventually attributes to the shifting. Positioner appliance is an alternative that can be utilized as pre/initial orthodontic treatment to accomodate the next treatment stage.